2012
DOI: 10.1155/2012/271914
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Applications of Magnifying Endoscopy with Narrow Band Imaging in the Stomach

Abstract: Narrow band imaging (NBI), in conjunction with magnifying endoscopy (ME), has arisen more and more attention in the area of advanced endoscopy. By enhancing the mucosal microvascular architecture and surface pattern, it is feasible to use ME-NBI to identify subtle changes associated with gastric inflammation, atrophy, intestinal metaplasia, and early gastric cancer. The new technique thus plays a valuable role in therapeutic decision-making, endoscopic treatment process, postoperative evaluation, and follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…22 However, the margins remain difficult to be predicted using NBI for undifferentiated carcinoma, since the tumor often grows horizontally, diffusely or thinly within the lamina propria before exposing on the mucosal surface. 27 On the contrary, a recent prospective study recommended the use of NBI in the diagnostic demarcation of undifferentiated EGC for its diagnostic accuracy reached 81.6%, which is higher than that of WLE (54.0%). 28 These conflicting results may be due to the diameter of the tumor, the profi-ciency of the endoscopist and different criteria used to define accuracy.…”
Section: Tumor Marginmentioning
confidence: 91%
See 1 more Smart Citation
“…22 However, the margins remain difficult to be predicted using NBI for undifferentiated carcinoma, since the tumor often grows horizontally, diffusely or thinly within the lamina propria before exposing on the mucosal surface. 27 On the contrary, a recent prospective study recommended the use of NBI in the diagnostic demarcation of undifferentiated EGC for its diagnostic accuracy reached 81.6%, which is higher than that of WLE (54.0%). 28 These conflicting results may be due to the diameter of the tumor, the profi-ciency of the endoscopist and different criteria used to define accuracy.…”
Section: Tumor Marginmentioning
confidence: 91%
“…In addition to the superior diagnostic rate reported in several studies, NBI can still help to achieve a better delineation of tumors with unclear margins in approximately 20% of the EGC by using both WLE and CE, and the combined use of NBI and CE makes the demarcation of the tumor easier . However, the margins remain difficult to be predicted using NBI for undifferentiated carcinoma, since the tumor often grows horizontally, diffusely or thinly within the lamina propria before exposing on the mucosal surface . On the contrary, a recent prospective study recommended the use of NBI in the diagnostic demarcation of undifferentiated EGC for its diagnostic accuracy reached 81.6%, which is higher than that of WLE (54.0%) .…”
Section: Tumor Marginmentioning
confidence: 99%
“…Clinically, the combination of magnifying endoscopy with narrow band imaging (commonly known as ME-NBI) may be used to detect antralization, although its performance needs to be further validated. Li et al 67 reported that under ME-NBI, the body-type mucosa presents as a honeycomb-like subepithelial capillary network (dark brown), with an oval dark glandular opening in the center and interspersed with spider-like collecting veins (Fig. 3a), whereas the antral-type mucosa presents as a curly or wavy subepithelial capillary network, with the spider-like collecting veins being rarely observed (Fig.…”
Section: Diagnosis Of Antralization and Its Implications In Clinical mentioning
confidence: 99%
“…Furthermore, few studies evaluating the usefulness of predicting invasion depth have been performed in cases of differentiated cancer. This is probably because undifferentiated cancer often spreads within the lamina propria sparsely before its exposure on the mucosal surface [38]. Another reason is that even patients with small undifferentiated cancers are more likely to undergo surgery than ESD.…”
Section: Limitations Of Nbimentioning
confidence: 99%